Functional Outcome Following Modular Endoprosthesis Reconstruction Surgery in Primary Bone Tumor of the Lower Limb - Sharil, Abdul Rahim (2008)
Introduction: Wide resection in Limb Salvage Surgery for primary bone tumors results in segmental osseous defect. The optimum method for reconstruction distal femur and proximal tibia remained controversial. Options include the use of autografts, allografts, custom-made megaprostheses and modular endoprostheses. Endoprosthesis allows early rehabilitation with a good long term functional outcome result. . The aim of this study is to evaluate the functional outcome of patient in modular endoprosthetic reconstructions surgery in the treatment of primary bone tumors of distal femur and proximal tibia of the lower limb, by using Musculoskeletal Tumor Society scoring system. Methods: Fifty four consecutive patients with primary bone tumor of distal femur and proximal tibia were selected and reviewed to determine the functional outcome after wide resection endoprosthesis reconstruction surgery by using Musculoskeletal Tumor Society scoring system. Results: There were 34 (63%) cases of distal femur and 20 (37%) cases of proximal tibia bone tumor. The Primary osteosarcoma are 33 (61.1%) and stage III GCT are 20 (37%). The mean age is 26.6±10.61. There were 12 (22.2%) patients who had met~tasis to the lung. The mean MSTS score for both DF and PT endoprosthesis was 21.13 (70.43%), MSTS score for DF was 21.94 (73.13%) and PT was 19.75 (65.83%) group into good to excellent result. The infection rate was 13% (7 cases) and high in PT endoprosthesis group. The early revision rate of endoprosthesis replacement was 11.1% (6 cases) mainly due to infection (3 cases). Infection and at site of endoprosthesis were the cause of early failure. Conclusion: Endoprosthesis replacement for primary bone tumors had good to excellence MSTS score. There were no different in functional outcome after distal femur endoprosthesis and proximal tibia endoprosthesis. The cause of early failure in our center following endoprosthesis surgery is infection and the location of endoprosthesis replacement which is a proximal tibia.